Impact of skeletonized harvesting of the internal thoracic artery on intrasternal microcirculation considering preparation quality. (1st July 2021) - Saemann, Lars; Zubarevich, Alina; Wenzel, Folker; Soethoff, Jasmin; Loganathan, Sivakkanan; Korkmaz-Icöz, Sevil; Karck, Matthias; Szabó, Gábor; Veres, Gábor
Abstract: : OBJECTIVES: Previous studies have demonstrated the impact of internal thoracic artery (ITA) harvesting on microcirculation in parasternal tissues. However, the impact of skeletonized ITA harvesting on intrasternal microcirculation is unknown. Intraskeletal tissue perfusion has been proven to be crucial for deep wound healing. Furthermore, the impact of different levels of surgical preparation quality on intrasternal microcirculation has not been investigated yet. METHODS: Sternal microcirculation (sLDP) was monitored with a novel Laser Doppler Perfusion needle probe, while the ITA was skeletonized in a pig model. To mimic different levels of preparation quality, satellite veins were either coagulated or not during preparation. To show the effect of ideally avoiding any surgical manipulation on sLDP, the ITA was clipped in a third sham-harvested group. RESULTS: sLDP was reduced highly significant to 71 [standard deviation (SD): 9]% ( P < 0.001) after skeletonized harvesting of the ITA. Coagulation of the satellite veins as a detrimental surgical factor resulted in a significantly stronger reduction of sLDP to 56 (SD: 11)% ( P < 0.05) compared to sLDP with non-coagulated satellite veins. ITA clipping reduced sLDP highly significant to 71 (SD: 8)% ( P < 0.001) in the sham-operated group. CONCLUSIONS: ITA harvesting markedly impairs microcirculation of the sternum but remains unavoidable when coronary artery bypass grafting should be performed. Nevertheless, excessive surgical damage and coagulation of satellite veins is avoidable and should be reduced to a minimum to minimize the risk of deep sternal wound healing complications. Abstract : Coronary artery bypass grafting (CABG) is a common cardiac surgical intervention to treat coronary heart disease.